Root canal treatment of three-rooted mandibular second premolar using cone-beam computed tomography - Mohammad Ahmad Alenezi; Mohammad Abdullah Tarish; Deena J Alenezi (Wolters Kluwer Medknow Publications, 2015)
A careful knowledge of root canals anatomy of different teeth is a corner stone for a successful outcome of root canal therapy. This reported case illustrates root canal therapy of a mandibular second premolar with three separated roots and root canals. An 18-year-old Saudi male presented for non-surgical endodontic treatment of mandibular right second premolar. Radiographic and clinical examinations revealed the presence of three roots and three root canals. The case was successfully managed with the help of cone-beam computed tomography (CBCT). In conclusion, the clinicians should always suspect the event of anatomical varieties and use all the available tools to diagnose and manage their cases.